DIALEKTIKA PENGUNGKAPAN IDENTITAS MANTAN ANGGOTA HIZBUT TAHRIR INDONESIA (HTI) KOTA MATARAM - Muhammad Syaoki (TASÂMUH, 2018)
The President formally issued Perppu No / 02 / Year / 2017 on Community Organizations. Then the Ministry of Law and Human Rights officially freeze the Hizb ut-Tahrir Indonesia (HTI) community organization because it is considered against the Pancasila. The impact of the government also directly prohibits all activities related to HTI. Kemendagri forbids all Civil Servants (PNS) to become HTI members, otherwise, their status as civil servants will be revoked. Even had also circulated a list of names of HTI members who served as civil servants of the State (ASN). This study aims to see the patterns of communication made by HTI members of Mataram city after the publication of Perppu No / 02 / Tahun / 2017 and freezing of HTI SK by Kemenkumham. The results of this study indicate that the HTI of Mataram responded to the release of Perppu no / 02/2017 and HTI freezing in several ways, including no longer using HTI identity when conveying the idea of Khilafah, abolishing the name of HTI in weekly bulletins dispersed in mosques but still explore the idea of Khilafah.